2014
DOI: 10.17795/bhs-22242
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Quercetin and Kaempferol as two Propolis Derived Flavonoids on Tyrosinase Enzyme

Abstract: Background: Tyrosinase is a copper-containing enzyme, which is widely distributed in microorganisms, animals and plants. It is also a key enzyme in melanin biosynthesis, which plays a crucial role in determining the color of mammalian skin and hair. In addition, unfavorable enzymatic browning of plant-derived foods by tyrosinase causes a decrease in nutritional quality and economic loss of food products. Objectives: In the present study the activity of this enzyme was examined against quersetin and kaempferol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In previous studies on flavonoids, compounds such as quercetin and kaempferol were shown to interfere with the activity of tyrosinase through chelation of copper in its active site [ 28 ]. It has been demonstrated that quercetin and kaempferol can suppress melanogenesis, directly inhibiting tyrosinase activity or reducing tyrosinase expression [ 45 ]. In our study, quercetin proved to be a good tyrosinase inhibitor, while kaempferol was a weaker inhibitor than arbutin.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies on flavonoids, compounds such as quercetin and kaempferol were shown to interfere with the activity of tyrosinase through chelation of copper in its active site [ 28 ]. It has been demonstrated that quercetin and kaempferol can suppress melanogenesis, directly inhibiting tyrosinase activity or reducing tyrosinase expression [ 45 ]. In our study, quercetin proved to be a good tyrosinase inhibitor, while kaempferol was a weaker inhibitor than arbutin.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was found that flavonoids containing the C4‐keto group or free hydroxyl group at the C3 position, e.g. quercetin and kaempferol, are also very effective tyrosinase inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…The enzyme has molecular weight of 120 kDa with two heavy (H) and two light (L) subunits of 43 and 14 kDa, respectively. Subunit H, contrary to subunit L, consists of an active site for copper ions (Hassani et al, 2018;Taherkhani and Gheibi, 2014). The enzyme has multiple catalytic functions, including mono-oxygenase (cresolase) activity (hydroxylation of monophenols to o-diphenols) and catechol oxidase activity (oxidation of o-diphenols to o-quinone) (Yin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Quinines can react with proteins and amino acids to form black or brown products (Sugumaran and Barek, 2016) or evolve chemically to form polyphenolic compounds or melanin (Gheibi et al, 2016;Ullah et al, 2016). Moreover, tyrosinase plays a key role in different processes such as melanin production in the skin, wound healing, agriculture, and cosmetic industry (Choi and Shin, 2016;Popoola et al, 2015;Taherkhani and Gheibi, 2014). The overactivity of the enzyme in the skin may lead to melanin overproduction and multiple skin disorders, including hyperpigmentation, depigmentation, and even melanoma (Choi and Shin, 2016;Popoola et al, 2015;Taherkhani and Gheibi, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation